14+5=-5x-6(-3x-15)+5

Simple and best practice solution for 14+5=-5x-6(-3x-15)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14+5=-5x-6(-3x-15)+5 equation:



14+5=-5x-6(-3x-15)+5
We move all terms to the left:
14+5-(-5x-6(-3x-15)+5)=0
We add all the numbers together, and all the variables
-(-5x-6(-3x-15)+5)+19=0
We calculate terms in parentheses: -(-5x-6(-3x-15)+5), so:
-5x-6(-3x-15)+5
We multiply parentheses
-5x+18x+90+5
We add all the numbers together, and all the variables
13x+95
Back to the equation:
-(13x+95)
We get rid of parentheses
-13x-95+19=0
We add all the numbers together, and all the variables
-13x-76=0
We move all terms containing x to the left, all other terms to the right
-13x=76
x=76/-13
x=-5+11/13

See similar equations:

| -2w=9/16 | | 4r+6+3=17 | | 6(d-75)=60 | | 8n-9=-137 | | -2+5b=-2 | | 3/8×x+7=13 | | y-(8y-11)=46 | | 4^-5x=2 | | 300p+300p-10+p-105=100 | | -10x+5x-3=-4x-x-x | | 1(6x-2)=5(x+1) | | 7n-(4n+9)=-15 | | 300p+300p-10+p-105=1000 | | 9/5=x/16 | | 300p+300p-10+p-105=10 | | -8h=-9h+2 | | 14+5=-5x-(-3x-15)+5 | | 2w+9=31/4 | | 3x3+4x2-32x=0 | | 2y+y+5=180 | | 300p+300p-10+p-105=1 | | -6x+14=-2x-6 | | 2n+(3n-8)=-28 | | 3r+-7=-1 | | 14+5=-5x—(-3x-15)+5 | | -2w+3/4=31/4 | | 11=y-(-4) | | 0.3=100/0.5^x | | 5x-2-3x=10-6 | | 2x-5(x+1)-3x=1 | | -0.5x+3=10 | | 5(-2z+5)=19z+16 |

Equations solver categories